SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEGAWAI UNTUK PROMOSI JABATAN STRUKTURAL MENGGUNAKAN METODE ANP DAN TOPSIS (STUDI KASUS: PT PLN (PERSERO) DISTRIBUSI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA) - , VIVIE DEYBY KUMENAP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT PLN (Persero) is a state owned enterprise which handles all aspects of electricity throughout Indonesia that required qualified human resources. The decision to determine an employee on an important position as a leader is not an easy job, because it will determine the success of the company in realizing its vision. To assist in determining the order of employees to choose from a number of employees who fit the required competency criteria by the company then a decision support system (DSS) is needed. DSS selection of employee for promotion of structural position utilizing Anlaytic Network Process (ANP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The main concept of ANP is influence to solve the problems of interdependence between alternatives or criteria, so the ANP can be used to determine the weight of criteria which have interdependence. The TOPSIS method is used to determine ranking of employee. The results of this research is an application used in the selection of employee for promotion based on criteria of competence that have been determined. The test results of the application can provide order of employees that can be used as an alternative decision for decision maker.